2012
DOI: 10.1007/s00343-012-1050-x
|View full text |Cite
|
Sign up to set email alerts
|

The decline process and major pathways of Microcystis bloom in Taihu Lake, China

Abstract: Eutrophication has become a serious concern in many lakes, resulting in cyanobacterial blooms. However, the mechanism and pathways of cyanobacteria decline are less understood. To identify and define the growth and decline of Microcystis blooms in Taihu Lake of China, and to illuminate the destination of surface floating blooms, we investigated the biomass distribution and variations in colony size, morphology, and floating velocity from October 2008 to September 2009. The results showed that the Microcystis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
(34 reference statements)
0
15
0
1
Order By: Relevance
“…Our previous study found a decline in Microcystis blooms occurred between July and August in Meiliang Bay of Lake Taihu, China (Wang et al, 2012). Certain decline processes and mechanisms were determined from this study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our previous study found a decline in Microcystis blooms occurred between July and August in Meiliang Bay of Lake Taihu, China (Wang et al, 2012). Certain decline processes and mechanisms were determined from this study.…”
Section: Discussionmentioning
confidence: 61%
“…Environmental factors were not considered as parameters in this niche model, effectively removing human error caused by the time difference between sample collection and data analysis and avoiding the effects of this time-lag on model construction. The Microcystis bloom was observed to decline in autumn (Wang et al, 2012). However, from fi eld data, the exact timing of this decline and the decline rate was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Excess inputs of nitrogen (N) and phosphorus (P) into lakes often result in eutrophication and affect the phytoplankton community structure (Vollenweider, 1970;Arhonditsis et al, 2003;Wang et al, 2012). As a result of eutrophication, harmful cyanobacterial blooms in water bodies frequently occurred and lead to a decrease in biodiversity (Meijer & Hosper, 1997;Wu et al, 2010) and a miniaturization trend in size distribution of phytoplankton (Ruggiu et al, 1998;Finkel et al, 2009;Ma et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Schöne et al (2010) found that the colonies in the water column were smaller than the colonies in the sediments of Quitzdorf Reservoir (Germany). Colony disaggregation was found during the bloom-decline process in Lake Taihu (China) (Wang et al 2012). The colony size of Microcystis also affects its vertical migration (Wang et al 2011), microcystin cell quota (Kurmayer et al 2003;Wang et al 2013a), and grazing resistance (White and Sarnelle 2014).…”
Section: Introductionmentioning
confidence: 99%